About the Places Where Ecotourism can be Developed in the Territory of Alat District of Bukhara Region of the Republic of Uzbekistan. (Eurasian Journal of Engineering and Technology, 2022)
This article states that it would be expedient to establish health-improving sanatoriums for human health on the shores of Dengizkul and Shurkul, and in the future to establish seasonal and non-seasonal ecotourism zones for the rational use and preservation of natural resources.